THE ROLE OF CULTURE, LANGUAGE, AND ETHICS IN GLOBAL BUSINESS - Michael Ba Banutu-Gomez (European Scientific Journal, ESJ, 2014)
Global business is the key to creating a better economy. Businesses across the globe need to work together in order to survive. Businesses need an understanding of other countries through research and implementation. Companies which devote time and effort to adapt to the countries they plan to do business in will be successful. Businesses need to realize that it takes more than a good speaker or savvy manager in order to compete in global business. Companies need to successfully understand three important aspects of business before they enter a foreign market. The three aspects are culture, ethics, and language. Understanding other countries culture, ethics and language are invaluable to creating a successful business internationally. These three aspects are the learning foundation of entering a foreign market and without them there will be no way to succeed. It takes time and commitment for a company to learn and understand the culture, ethics, and language of a potential country. No amount of studying and research will be able to show the company the rules and norms a certain country lives by. These aspects of culture, language, and ethics can only fully be understood through firsthand experience. All the training and education a company injects into their employees is useless unless there is total commitment from the managers and employees to prepare for conducting business abroad. Some aspects of global business are similar to taking a class abroad. The reason you take a class in another country is to broaden your skills and improve your understanding of other places. The traditions of a countries culture are essential to the student’s success in studying in that particular county. This is similar to the norms and cultural quirks which businesses must understand in order to be successful in other countries.